Neurodegenerative Disease: What Potential Therapeutic Role of Acid-Sensing Ion Channels? - Mango, Dalila; Nisticò, Robert (Frontiers in Cellular Neuroscience, 2021)
Acidic pH shift occurs in many physiological neuronal activities such as synaptic transmission and synaptic plasticity but also represents a characteristic feature of many pathological conditions including inflammation and ischemia. Neuroinflammation is a complex process that occurs in various neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Multiple Sclerosis and Huntington’s disease. Acid sensing ion channels (ASICs) represent a widely expressed pH sensor in the brain that play a key role in neuroinflammation. On this basis, acid-sensing ion channel blockers are able to exert neuroprotective effects in different neurodegenerative diseases. In this review we discuss the multifaceted roles of ASICs in brain physiology and pathology and highlight ASIC1a as a potential pharmacological target in neurodegenerative diseases.